2020
DOI: 10.1093/jee/toaa020
|View full text |Cite
|
Sign up to set email alerts
|

A Day in the Life: Identification of Developmentally Regulated MicroRNAs in the Colorado Potato Beetle (Leptinotarsa decemlineata; Coleoptera: Chrysomelidae)

Abstract: The Colorado potato beetle (Leptinotarsa decemlineata (Say)) is an important pest of the cultivated potato (Solanum tuberosum (L.) [Solanales: Solanaceae]). With its broad resistance toward commonly used insecticides, it is clear that more sophisticated control strategies are needed. Due to their importance in insect development, microRNAs (miRNAs) represent a potential tool to employ in insect control strategies. However, most studies conducted in this area have focused on model species with well-annotated ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 104 publications
1
4
0
Order By: Relevance
“…All putative CPB miRNAs targeting the CPB‐ADAM10 gene identified in CPB larvae feeding on potato cv. Vivaldi in the present work were also detected by Wiebe et al 38 . in all stages of development of CPB feeding on potato cv.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All putative CPB miRNAs targeting the CPB‐ADAM10 gene identified in CPB larvae feeding on potato cv. Vivaldi in the present work were also detected by Wiebe et al 38 . in all stages of development of CPB feeding on potato cv.…”
Section: Discussionsupporting
confidence: 88%
“…In CPB, the miRNA profile has been shown to change throughout development 38 and in adult beetles differentially expressed miRNAs were identified in response to environmental and chemical stresses such as low temperatures 39 and exposure to imidacloprid 40 . To explore the potential regulation of the CPB‐ADAM10 gene by miRNAs in CPB larvae feeding on potato cv.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing-based study revealed 14 upregulated and 19 downregulated miRNAs in this potato pest treated to imidacloprid ( Morin et al 2017b ). Assessment of miRNA expression in different stages of L. decemlineata development revealed multiple conserved and novel miRNAs as well as identified putative roles underlying insecticide resistance for select miRNAs ( Wiebe et al 2020 ). While multiple reports support modulation of miRNAs in insects exposed to insecticides, information is sparse regarding differential expression of piRNAs following similar treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study using whole-genome sequencing and transcriptomics information highlighted comparable genetic pathways, but different genes, used by L. decemlineata to develop insecticide resistance [ 58 ]. Finally, it is noteworthy to mention information stemming from different groups that revealed miRNAs, short non-coding transcripts that can regulate gene expression in a posttranscriptional manner, with potential roles for insecticide resistance and response in L. decemlineata [ 59 , 60 ]. Overall, it is clear from the molecular players presented in this section that many leads with a likely relevance for insecticide resistance in L. decemlineata have emerged over the past decade.…”
Section: Molecular Players Associated With Insecticide Resistance In ...mentioning
confidence: 99%